2001
DOI: 10.1161/hq0801.093507
|View full text |Cite
|
Sign up to set email alerts
|

Electron Paramagnetic Resonance Investigation on Modulatory Effect of 17β-Estradiol on Membrane Fluidity of Erythrocytes in Postmenopausal Women

Abstract: Abstract-Many studies have shown that estrogen may exert cardioprotective effects and reduce the risk of hypertension and coronary events. On the other hand, it has been proposed that cell membrane abnormalities play a role in the pathophysiology of hypertension, although it is not clear whether estrogen would influence membrane function in essential hypertension. The present study was performed to investigate the effects of 17␤-estradiol (E 2 ) on membrane fluidity of erythrocytes in normotensive and hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 32 publications
7
75
0
Order By: Relevance
“…The RBC preparation and ESR measurement procedures have been described previously. [9][10][11][12][13] We evaluated the values of outer and inner hyperfine splitting (2T' ││ and 2T' ⏊ in G, respectively) in the ESR spectra for the spin label agent (5-nitroxide stearate, Aldrich Co. Ltd., Milwaukee, Wisconsin, USA) and calculated the order parameter (S). [9][10][11][12][13] The greater the value of the order parameter (S) was, the lower the membrane fluidity of RBCs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The RBC preparation and ESR measurement procedures have been described previously. [9][10][11][12][13] We evaluated the values of outer and inner hyperfine splitting (2T' ││ and 2T' ⏊ in G, respectively) in the ESR spectra for the spin label agent (5-nitroxide stearate, Aldrich Co. Ltd., Milwaukee, Wisconsin, USA) and calculated the order parameter (S). [9][10][11][12][13] The greater the value of the order parameter (S) was, the lower the membrane fluidity of RBCs.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12][13] We evaluated the values of outer and inner hyperfine splitting (2T' ││ and 2T' ⏊ in G, respectively) in the ESR spectra for the spin label agent (5-nitroxide stearate, Aldrich Co. Ltd., Milwaukee, Wisconsin, USA) and calculated the order parameter (S). [9][10][11][12][13] The greater the value of the order parameter (S) was, the lower the membrane fluidity of RBCs. [9][10][11][12][13] Plasma 8-Iso-PG F2α levels were determined by using an enzyme immunoassay (Cayman Chemicals Co., Ann Arbor, Michigan, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In a study presented earlier, we showed that E2 increased membrane fluidity (a reciprocal value of membrane microviscosity) of erythrocytes and improved the rigidity of cell membranes in postmenopausal women via the NO-dependent mechanism. 3 Because abnormalities in membrane microviscosity could cause a disturbance in the rheological behavior of erythrocytes and the microcirculation, estrogen might be favorable for the prevention of circulatory disorders in postmenopausal women. In addition, we demonstrated that progesterone and NO might have a synergistic effect on the improvement of membrane microviscosity of erythrocytes.…”
Section: A New Hormone Therapy With Drospirenone and No Production Inmentioning
confidence: 99%